Editors’ Note - Cohn, Ellen R.; Cason, Jana (International Journal of Telerehabilitation, 2023)
The International Journal of Telerehabilitation (IJT) is a biannual journal dedicated to advancing telerehabilitation by disseminating peer-reviewed information about current research and practices. IJT is indexed by PubMed and Scopus. IJT is published via the open journal system (OJS) and sponsored by the University of Pittsburgh’s Office of Scholarly Communication and Publishing at the University Library System.